1994
DOI: 10.1093/treephys/14.6.647
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term ozone exposure and soil water availability on the carbon economy of juvenile Douglas-fir

Abstract: Effects of ozone and soil water availability on partitioning and translocation of assimilates were studied in three-year-old Douglas-fir (Pseudotsuga menziesii [Mirb.] Franco) seedlings exposed, in separate experiments, to 0 and 106 or 0 and 514 micro g m(-3) ozone for 8 h day(-1) for 9 days. The dynamics of carbon from assimilated (14)CO(2) were followed. No interactions between ozone and soil water content were observed. Total net uptake of carbon was reduced by low soil water content, but was unaffected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A lower leaf sucrose export and higher carbohydrate level would lead to feedback regulation of photosynthesis and therefore partly explain the reduction in carbon assimilation. Several works have shown a decrease in allocation to roots and root to shoot biomass ratio in response to O 3 (Gorissen et al 1994;Grantz and Farrar 2000;Grantz and Yang 2000;Rennenberg et al 1996;Spence et al 1990). Given that mature leaves preferentially allocate carbon resources to stems and roots (Gordon and Larson 1970;Matyssek et al 2010b;Rangnekar and Forward 1969), it appears logical that the O 3 -induced early senescence would primarily affect root growth.…”
Section: O 3 -Induced Signalling In Treesmentioning
confidence: 99%
“…A lower leaf sucrose export and higher carbohydrate level would lead to feedback regulation of photosynthesis and therefore partly explain the reduction in carbon assimilation. Several works have shown a decrease in allocation to roots and root to shoot biomass ratio in response to O 3 (Gorissen et al 1994;Grantz and Farrar 2000;Grantz and Yang 2000;Rennenberg et al 1996;Spence et al 1990). Given that mature leaves preferentially allocate carbon resources to stems and roots (Gordon and Larson 1970;Matyssek et al 2010b;Rangnekar and Forward 1969), it appears logical that the O 3 -induced early senescence would primarily affect root growth.…”
Section: O 3 -Induced Signalling In Treesmentioning
confidence: 99%
“…There has been much interest in the relative magnitudes and interactive effects of these two stresses (Gorissen, Joosten, Smeulders, & Van Veen, 1994;Matyssek et al, 2006;Pääkkönen, Vahala, Pohjola, Holopainen, & Kärenlampi, 1998), while previous research results were inconsistent. Dixon, Thiec, and Garrec (1998) showed that a drought relieved the effects of O 3 on beech (Fagus sylvatica L.), but not on Norway spruce (Picea abies (L.) H.…”
mentioning
confidence: 99%
“…The development of roots is often dependent on the availability of photosynthate, while carbon-limiting factors such as ozone affect the root growth rapidly and significantly (Andersen 2003). Therefore, a possible reason for the reductions of root elongations is the stress caused by ozone exposure, since ozone stress affects the photosynthetic activity of plants causing a reduction in carbon allocation to roots (Cooley and Manning 1987;Spence et al 1990;Gorissen et al 1994;Rennenberg et al 1996). Further, the ozone stress can reduce carbon fixation, alter leaf and root respiration rates, shift the partitioning of carbon into different chemical forms, and disrupt carbon and nutrient allocation patterns (Chappelka and Samuelson 1998).…”
Section: Discussionmentioning
confidence: 99%